Effect of UV-B radiation on plant litter decomposition in a tropical ecosystem on the north coast of the State of Sao Paulo, southeast Brazil - Marinho, Osmarina Alves (2017)
The solar radiation in general and UV radiation in particular has been recognized to stimulate plant litter decomposition through photochemical mineralization of photosensitive organic molecules, such as lignin, facilitating microbial decomposition, with great relevance role in dryland ecosystems where microbial activity is low, however little is known about how photodegradation could influence other ecosystems without moisture limitations and under what conditions may be favored, therefore the mechanisms has not yet been established. Decomposition in tropical ecosystem is a complex process and can be induced by a number of environmental factors with certain differences when compared to arid and semi-arid ecosystems. To assess the mechanisms underlying UV-B photodegradation, we designed a 300 days field experiment at a tropical ecosystem with high levels of annual precipitation and exposure litter to three levels of radiation combined with a biocide treatment. Results show that the removal of UV-B radiation decelerated plant litter decomposition during the later stage compared to litter exposure to full sun, however shaded litter had similar mass loss compared to litter exposed to full sun. Furthermore, differences in the decay constant among radiation treatments due to UV-B effect is independent of lignin loss. Overall, our study suggest that UV-B contributes to the plant litter decomposition through carbon losses, however, had no effect on nitrogen, neither lignin nor cellulose loss. However, more studies are needed in order to investigate the positive and negative effects of UV exposure on microbial activity in tropical ecosystems.